Randomized Trial of Fetal Surgery for Severe Left Diaphragmatic Hernia. Issue 1 (March 2022) - Deprest, J.A.; Nicolaides, J.H.; Benachi, A.; Gratacos, E.; Ryan, G.; Persico, N.; Sago, H.; Johnson, A.; Wielgoś, M.; Berg, C.; Van Calster, B.; Russo, F.M.
Abstract : ( Engl J Med . 2021;385:107–118) Congenital diaphragmatic hernia (CDH) can lead to serious lifelong complications, but may be treated if diagnosed before birth. In fetoscopic endoluminal tracheal occlusion (FETO), a balloon is inserted into the fetal trachea in utero to stimulate fetal lung growth and is removed prior to birth. One study of 210 fetuses undergoing FETO for severe lung hypoplasia due to isolated CDH found a nearly doubled survival rate among fetuses who received FETO compared with controls (49% vs. 24%). This current study, Tracheal Occlusion to Accelerate Lung Growth (TOTAL), aimed to test whether fetuses with surgical treatment of severe left CDH had superior survival rates compared with fetuses who received expectant prenatal care.